The Influence of Productive Zakat Distribtion, Business Development and Business Capital on the Development of Mustahik Micro-Business at BAZNAS Bangkalan Regency - Nailul Rahmawati; Abdur Rohman; Faizal Amir (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the effect of productive zakat distribution, business development, and business capital on the development of micro-businesses of mustahik in BAZNAS Bangkalan Regency. Productive zakat is one of the instruments in empowering the people's economy which is given to mustahik with the hope of increasing economic independence through micro-businesses. This study is quantitative in nature using random sampling techniques in the form of observation data and filling out questionnaires to 65 mustahik who received productive zakat funds through the Bangkalan Makmur Baznas Bangkalan Regency program. The data were analyzed using descriptive analysis methods and using quantitative methods in order to determine the effect of providing productive zakat funds to mustahik using multiple regression tests. The results of the study indicate that the distribution of productive zakat, business development, and business capital significantly affect the development of micro-businesses of mustahik. Targeted productive zakat can increase working capital, while business development plays a role in improving business skills and management. In addition, sufficient business capital encourages more stable business growth. Keywords: Productive Zakat, Business Development, Business Capital, Micro Business Development, Mustahik